A contrastive analysis of rhetorical structures of English and Vietnamese linguistic research articles - Hong, Nguyen Bich; Pham, Hien (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper reports a contrastive genre analysis of rhetorical structures of linguistic research articles written in English and Vietnamese. The quantitative method was employed with data from a corpus of 35 English and 35 Vietnamese research articles randomly selected from internationally and Vietnamese reputable journals of linguistics published in the five-year period from 2015 to 2019. The rhetorical model of research articles in Applied Linguistics, as suggested by Pho (2008), was applied as a framework to analyse the corpus of this study. Findings reveal some similarities and differences in the structure of English and Vietnamese research articles. Generally, the macro-structure of Vietnamese articles is basically similar to that of English articles. However, in English articles, there are often more parts than in Vietnamese ones, and the discussion tends to be separated into a single section. The findings of this study can shed some light on the path of graduate students and novice scholars, especially Vietnamese researchers, who strive to publish their scientific achievements in reputable journals so that they will be accepted as new dwellers of the linguistic community.